PERAN REBRANDING DESTINASI WISATA TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN DI TOGA HILL KABUPATEN SUMEDANG - Ardiansyah, Mochamad Rival; Supriyadi, Tedi; Pratama, Gilang (STAH Dharma Sentana Sulawesi Tengah, 2024)
Rebranding is creating a new name, term, symbol, design or a combination of all of them for a brand that is not denied with the aim of developing a differentiated (new) position in the minds of stakeholders and competitors. Rebranding has five indicators, namely, repositioning, renaming, redesign, and relaunch. This researcher analyzes Rebranding as variable X with visiting decisions as variable Y. This study aims to determine the description and detail the role of destination rebranding on tourist visiting decisions to Toga Hill. The type of research used is quantitative research with a descriptive approach and this research is included in correlation research. This research uses a survey method with probability sampling method, with a total of 100 respondents who have visited Toga Hill. This study produces answers that Rebranding plays a role in tourist visiting decisions. And tourists also agree that many tourists visit Toga Hill